PCSK9 inhibitors: effectiveness of treatment and changes in background lipid-lowering therapy in a real world Italian population. The AT-TARGET-IT study. (3rd October 2022) - Perrone-Filardi, P; Basile, C; Asile, G; Abbate, C; Catalano, A; Merlini, P A; Calabro', P; Iannuzzo, G; Ciccone, M M; Paloscia, L; Varbella, F; Brunetti, N D; et al.
Abstract: Introduction: PCSK9 inhibitors (PCSK9i) significantly decrease LDL cholesterol (LDL-C), either as monotherapy or in addition to the maximally tolerated dose of statin and/or ezetimibe. Yet, few data are available on efficacy and background lipid-lowering therapy (LLT) adjustment in patients treated with PCSK9i in real-world observations. Purpose: AT-TARGET-IT is an Italian multicenter registry involving 9 Italian centers, designed to assess efficacy, adherence, and persistence of PCSK9i, as well as prescribing doctors' behavior in patients with atherosclerotic cardiovascular disease (ASCVD) or familial hypercholesterolemia (FH). The aim of the present analysis was to assess efficacy and changes in background LLT therapy in patients on PCSK9i in a real-world single country observation. Methods: From June through November 2021, we enrolled patients with PCSK9i first prescription from 6 months before inclusion through starting of PCSK9i use. Clinical and demographic characteristics, concomitant therapies, blood chemistry, were recorded at the time of first prescription and at the latest observation preceding inclusion in the study. Background therapy was assessed at baseline and during follow-up, evaluating treatment withdrawal, reduction of doses, or changes from statin-ezetimibe association to single drug therapy. Results: We enrolled 798 patients (27% with FH) receiving either alirocumab or evolocumab and followed for a median time of 19.3 months. At the time of PCSK9i first prescription LDL-C was 147.6 mg/dl and reached 51.5 mg/dl at the time of latest observation (64% reduction), and 129 patients (16%) were not receiving any LLT, 669 patients received background LLT, of them 246 (31%) were taking ezetimibe alone and 423 (53%) were taking statins with or without ezetimibe. At the end of the observation period, 785 patients (98%) were still receiving PCSK9i and 550 (69%) did not change background LLT. Of 248 patients changing background LLT, 116 (47%) withdrew therapy, 132 (53%) changed dose or type of LLT. After stratification by achievement of LDL-C target according CV risk class, 483 patients achieved the target (60%). Target was achieved at the end of the observation period in 63% of patients taking triple therapy, 65% patients receiving PCSK9i plus statins, 62% of patients receiving PCSK9i plus ezetimibe and 55% receiving PCSK9i alone (Figure 1). No significant differences in terms of percentage of patients changing background LLT during PCSK9i treatment were found between patients at target for LDL-C and those not at target. Conclusion: AT-TARGET-IT study shows that PCSK9i therapy is effective in reaching LDL-C target in the majority of patients, yet a sizable number of them (40%) remains undertreated. LLT background therapy is either reduced or withdrawn in 31% of patients, being responsible for not reaching target. Reasons for inappropriate LLT changes in patients receiving PCSK9i should be identified and removed to optimize lipid control. Funding Acknowledgement: Type of funding sources: None.